2013
DOI: 10.1186/1471-2407-13-84
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and innovative Radiation Treatment FOR improving Cancer treatment outcomE (ARTFORCE); a randomized controlled phase II trial for individualized treatment of head and neck cancer

Abstract: BackgroundFailure of locoregional control is the main cause of recurrence in advanced head and neck cancer. This multi-center trial aims to improve outcome in two ways. Firstly, by redistribution of the radiation dose to the metabolically most FDG-PET avid part of the tumour. Hereby, a biologically more effective dose distribution might be achieved while simultaneously sparing normal tissues. Secondly, by improving patient selection. Both cisplatin and Epidermal Growth Factor Receptor (EGFR) antibodies like Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…The authors of the ARTFORCE phase II study designed their dose escalation sub-volumes based on 50% of the maximum uptake in the primary tumor plus a 3 mm margin to create a final PTV-FDG-PET. [14] Investigators from Ghent University Hospital implemented different strategies in two phase I dose escalation studies, using focal dose painting by contours based on the source-to-background ratio in one study[15] and dose painting by number in the second study. [16]…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the ARTFORCE phase II study designed their dose escalation sub-volumes based on 50% of the maximum uptake in the primary tumor plus a 3 mm margin to create a final PTV-FDG-PET. [14] Investigators from Ghent University Hospital implemented different strategies in two phase I dose escalation studies, using focal dose painting by contours based on the source-to-background ratio in one study[15] and dose painting by number in the second study. [16]…”
Section: Introductionmentioning
confidence: 99%
“…The higher acute disease control, with a 3-7 % superior PFS, as shown in four published randomized clinical comparing CMT vs. chemotherapy alone in early-stage HL [ 61 -64 ], did not translate to an improvement in OS of CMT. On the contrary, the fi nal analysis of the National Cancer Institute of Canada Clinical Trials Group (NCIC-CTG) and Eastern Cooperative Oncology Group (ECOG) HD.6 study showed superior OS for chemotherapy alone at 12 years, due to increased late events/ toxicity in the CMT arm [ 65 ]. Similarly, the GHSG in the HD10/11 trials while showing an improved long-term disease control (8-y time to treatment failure) was unable to show an advantage in OS for patients treated with CMT as compared to chemotherapy alone [ 66 ].…”
Section: Phase II Concluded Studies In Early-stage Diseasementioning
confidence: 99%
“…These new methods increased the effectiveness of this treatment modality which delivered much smaller doses to critical organs such as the lung, heart, and breast [61]. So far only a few clinical trials have been conducted in which dose escalation was prescribed on an FDG avid area within the GTV [64][65][66][67]. In the modern era of conformal radiotherapy, TNI and the EFRT are no longer in practice and supplanted by limited-field radiation therapy: IFRT, if the RT field encompasses all of the clinically involved nodal regions, and INRT, with an assumption to deliver the dose only to the initially involved nodes, rather than including the entire region of the involved nodal chain.…”
Section: Applications In Radiation Oncologymentioning
confidence: 99%
“…The multicentre randomized Phase II PET Boost trial in NSCLC (PET Boost, NCT01024829) thus far has reported no increase in toxicity. 72 Moreover, a Phase III randomized study in HNSCC is investigating the redistribution of the radiation dose to the metabolically most 18 F-FDG-PETavid part of the tumour (ARTFORCE, ClinicalTrials.gov identifier: NCT01504815 73 ).…”
Section: Functional Bioimage-tailored Radiotherapy For Head and Neck mentioning
confidence: 99%